2012
DOI: 10.1016/j.jchromb.2012.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 8-hydroxy-2′-deoxyguanosine in human urine using hydrophilic interaction chromatography with tandem mass spectrometry

Abstract: Urinary 8-hydroxy-2'-deoxyguanosine (8-OHdG) is a widely used noninvasive biomarker of oxidative stress. A selective, sensitive and rapid method for determining 8-OHdG in human urine was developed using hydrophilic interaction chromatographytandem mass spectrometry (HILIC-MS/MS) with electrospray ionization. 8-OHdG and isotopically labeled 8-OHdG (internal standard) were separated on a HILIC column with a mobile phase of 10 mM ammonium acetate : acetonitrile (1 : 9, v/v) within 10 min and detected by using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The LOD was 1 fmol and the LOQ was 3 fmol, which is consistent with the result obtained by HILIC method53. This indicated that the sensitivity of the analytical method developed was excellent.…”
Section: Resultssupporting
confidence: 89%
“…The LOD was 1 fmol and the LOQ was 3 fmol, which is consistent with the result obtained by HILIC method53. This indicated that the sensitivity of the analytical method developed was excellent.…”
Section: Resultssupporting
confidence: 89%
“…In light of our findings, we recommend that thawing at 37 °C is a necessary part of sample preparation for the analysis of oxidized guanine lesions in urine. Previous reports in the literature have used a variety of sample workup steps e.g., thawing of urine at RT [36] , removal of precipitates by filtration or centrifugation [38] , [46] , and diluting the urine with deionized water [47] prior to analysis. We speculate these steps may contribute to some of the apparent assay variability between laboratories, as noted previously [48] , [49] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the degree of DNA damage has been assessed by the measurement of 8-OH-dGuo in biological fluids by LC-MS or ELISA methods [6,14] Scarce data are available on other products of the oxidation of nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Our method consists of sample pre-treatment with solid phase extraction (SPE) followed by chromatographic separation, with a 14 HILIC column, by UHPLC-MS/MS. In recent years, hydrophilic interaction chromatography (HILIC) has been reported as a good alternative to reversephase liquid chromatography (RPLC) for the separation of highly polar compounds such as nucleotides and their derivatives [6,14]. In our experience, SPE is essential to facilitate the subsequent detection and quantification of metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation